Penerapan Teori Heuristika Hukum dalam Sistem Peradilan Pidana di Indonesia - Syarif Fadillah (Jurnal Hukum Jurisdictie, 2021)
Teori Heuristika berasal dari kata heuriskein (Yunani), dalam bahasa latin heuristicus yang berarti “to find out” atau “discover”. It's to find something. Heuristika is serving to find out or discover or attempt to discover (something new knowledge). In another sense, heuristika is "the branch of logic which treats of the art of discocery or invention" (a branch of logic that deals with the art of discovering a new knowledge). According to Prof. Dr. Syarifuddin, SH. MH., (Chairman of the Supreme Court of Indonesia), when dismissing Pidoto during his inauguration as a professor not fixed at the Faculty of Law, Diponegoro University Semarang, told his fellow judges throughout Indonesia, in deciding the case of criminality should not only fixate on the mormative rules alone, must think holistically and preogresif by putting forward human values in realizing true justice. From the expression of the Chief Justice, in the practice of the Criminal Justice System in Indonesia, has the theory of Heuristika Law has been applied? If you look at the formil criminal law regulations that apply in Indonesia, namely Law No. 8 of 1981, on the Criminal Procedure Law Law, the sabenarnya Heuristika Hukum already exists in the concept of Akusatoir and The Principle of Diversion with Restorative Justice. Even in the criminal act of Corruption, the Supreme Court of Indonesia has issued PERMA No. 1 of 2020 on The Guidelines for Prosecution for Corruptors. Perma, according to the Chief Justice of the Supreme Court, is an effort to apply the theory of heuristika law in the enforcement of corruption crimes. But we realize that in practice there are still only examiners, prosecutors and judges, who still use the ways of the concept of Inkisatoir and only guided by laws and regulations only in the process of law enforcement, without looking more deeply into human values. For this reason, the theory of heuristika law must be applied and / or used by law enforcement, from the stage of investigation, prosecution and the process of making a decision. Even at the execution stage until it comes back to society.